Clinical evaluation, accurate diagnosis and treatment of four pedigrees with Fabry's disease - Gou, Peng; Leng, Jie; Cheng, Xinran; Zhang, Jing (Frontiers in Pediatrics, 2023)
Objective This article analyze the data of 4 families with mutations of GLA (galactosidase) gene，with a special focus on the clinical presentation, diagnosis and interdisciplinary clinical management of Fabry's disease (FD) and Enzyme Replacement Therapy (ERT) treatment, aim to assess more accurate prevention and treatment strategy. Methods The MSSI (Mainz Severity Score Index) scale was used to evaluate clinical data in 5 children diagnosed in our Hospital, and genotypes of all FD patients were collected. Two male children started ERT, we summarized the clinical effect and the evaluation of globotriaosylsphingosine (Lyso-GL-3) before and after treatment. Results Five children passed the family histories, clinical manifestations, α-galactosidase A (a-Gal A) activity and genetic test results confirmed FD. Two children used Agalsidase α every 2 weeks regularly, after ERT, their clinical symptoms were improved, the pain intensity was significantly relieved, and the re-examination Lyso-GL-3 decreased conspicuously, and no serious adverse reactions occurred. Conclusion The clinical phenotype of FD in childhood is nonspecific, and the misdiagnosis rate is fabulous high. Most children with FD delay diagnosis for a long time, and many organs are seriously damaged in adulthood. Pediatricians improve their diagnosis and treatment awareness, screen high-risk groups, and emphasize multidisciplinary cooperation and whole life cycle management after diagnosis. As the guardian of the first stop of the patient's life cycle, it is worth discussing when to start ERT. The diagnosis of the proband is also conducive to the mining of other cases of FD families and has important guiding significance for prenatal diagnosis.